2019
DOI: 10.1002/jpen.1593
|View full text |Cite
|
Sign up to set email alerts
|

A Single Urine Sodium Measurement May Validly Estimate 24‐hour Urine Sodium Excretion in Patients With an Ileostomy

Abstract: Background Sodium deficiency in patients with an ileostomy is associated with chronic dehydration and may be difficult to detect. We aimed to investigate if the sodium concentration in a single spot urine sample may be used as a proxy for 24‐hour urine sodium excretion. Methods In a prospective observational study with 8 patients with an ileostomy and 8 volunteers with intact intestines, we investigated the correlations and agreements between spot urine sodium concentrations and 24‐hour urine sodium excretions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…They found that such consultations significantly reduced the rate of hospital readmissions associated with high-secreting stoma and dehydration, which also resulted in significant savings for the hospital [ 13 ]. Other researchers have reached similar conclusions, citing HOS as the most common cause of readmission [ 37 , 38 , 39 ]. Many researchers reported significantly lower rates of patients returning to the hospital after implementation of a follow-up nutritional consultation compared to the non-intervention group in a retrospective study compared to other researchers [ 13 , 43 , 44 , 45 ].…”
Section: Nutrition Issuessupporting
confidence: 54%
See 2 more Smart Citations
“…They found that such consultations significantly reduced the rate of hospital readmissions associated with high-secreting stoma and dehydration, which also resulted in significant savings for the hospital [ 13 ]. Other researchers have reached similar conclusions, citing HOS as the most common cause of readmission [ 37 , 38 , 39 ]. Many researchers reported significantly lower rates of patients returning to the hospital after implementation of a follow-up nutritional consultation compared to the non-intervention group in a retrospective study compared to other researchers [ 13 , 43 , 44 , 45 ].…”
Section: Nutrition Issuessupporting
confidence: 54%
“…On the other hand, patients with an ileostomy who do not have this problem, and patients with a colostomy should follow the principles of a healthy diet, e.g., not overdoing the supply of salt, monitoring for signs of dehydration and checking sodium levels prophylactically [ 23 , 38 ]. Pedersen et al [ 39 ] report that in patients with an ileostomy, a single spot urine sodium sample taken in the morning to noon hours can reliably estimate the 24-h urine sodium excretion. Testing this in people with an ileostomy can, therefore, quickly identify a sodium deficiency and the sodium supply can be increased, if needed [ 39 ].…”
Section: Nutrition Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Urine sodium will be low when body fluid status is uncorrected. Fractional sodium excretion is a more accurate marker of sodium status because it is independent of urine flow [ [93] , [94] , [95] ]. Progressive weight loss and dehydration are common at disease onset, and acute renal failure may develop in patients with delayed diagnosis [ 96 ].…”
Section: Diet-induced Diarrheasmentioning
confidence: 99%